Čas ne teče za vse enako - Perger, Nina (Družboslovne razprave, 2021)
In the article, we discuss the COVID-19 epidemic-related lockdown in Slovenia during March and May 2020. We focus on a specific social group: solo-living women. We aim to answer two research questions: how did different age groups of solo-living women experience the pandemic and the pertaining protective measures, and which resources and coping strategies did they report? A practical implication of our study is the evidence-based recommendation that the planning and implementation of protective measures should pay close attention to youth and young adults since they are exposed to a particular socio-psychological vulnerability, amplified by certain circumstances and social expectations interrelated with their phase in their life trajectory.
Keywords: affective experiences; Covid-19; doživljanje; Epidemics; Epidemije; lockdown; resources and coping strategies; solo-living women; viri in strategije spoprijema; zaustavitev javnega življenja; ženske, ki živijo same